Microsurgical Reconstruction of Extensive Oncological Scalp Defects - Goertz, Ole; von der Lohe, Leon; Martinez-Olivera, Ramón; Daigeler, Adrien; Harati, Kamran; Hirsch, Tobias; Lehnhardt, Marcus; Kolbenschlag, Jonas (Frontiers in Surgery, 2015)
While most small to medium defects of the scalp can be covered by local flaps, large defects or complicating factors like a history of radiotherapy often require a microsurgical reconstruction. Several factors need to be considered in such procedures. A sufficient preoperative planning is based on adequate imaging of the malignancy and a multi-disciplinary concept. Several flaps are available for such reconstructions, of which the latissimus dorsi and anterior lateral thigh flaps are the most commonly used ones. In very large defects, combined flaps such as a parascapular / latissimus dorsi flaps can be highly useful or necessary. The most commonly used recipient vessels for microsurgical scalp reconstructions are the superficial temporal vessels, but various other feasible choices exist. If the concomitant veins are not sufficient, the jugular veins represent a safe backup alternative but require a vessel interposition or long pedicle. Postoperative care and patient positioning can be difficult in these patients but can be facilitated by various devices. Overall, microsurgical reconstruction of large scalp defects is a feasible undertaking if the mentioned key factors are taken into account.